Interventions for reducing antimicrobial resistance in livestock in sub Saharan Africa: systematic review - Jacobsen, Alice B. J. E.; Ogden, Jane; Ekiri, Abel B. (Frontiers in Veterinary Science, 2025)
IntroductionAlthough antimicrobial resistance (AMR) threatens the entire world, it disproportionately affects Low- and Middle-Income countries. The animal sector is a contributor to AMR and interventions for reducing AMR in this sector exist. However, in sub-Saharan Africa, there is limited information on AMR interventions targeting livestock.MethodsA systematic review was conducted following the PRISMA checklist to evaluate the existing evidence on AMR interventions, outcomes, motivators and barriers to adoption, and the strengths and weaknesses, with a focus on farmers and animal health professionals. The databases Web of Science, Scopus, and PubMed were searched. The articles were categorised into seven groups based on outcome measures: change in antimicrobial use (AMU) practices; change in AMR level; change in antimicrobial stewardship (AMS) practices; change in attitudes and perceptions concerning AMU, AMR, and AMS; change in knowledge concerning AMU, AMR, and AMS; change in surveillance strategies; and other.Results and discussionA total of 546 articles were considered and, in the end, only five articles were eligible. The reported interventions focused on change in knowledge (3/5), change in AMS practices (2/5), surveillance (AMR and AMU) (2/5), and change in development of AMR (1/5). The motivators for adoption of interventions included social desirability and the barriers included lack of finance and lack of perceived sustainability of the interventions. The observed strengths of the reviewed studies included the use of One Health approaches, collaboration between researchers and the community, and involvement of a diverse study population. The observed weaknesses included self-reporting of outcome measures and lack of clarity in reporting. The financial impact and societal impact were not documented in any of the reported interventions. However, organisation culture was highlighted as having a positive impact on adoption of interventions in one study. The quality of the study designs was generally considered low.ConclusionThe findings revealed there is limited evidence on AMR interventions in the animal sector in Africa especially those focussed on change in AMU and change in development and/or spread of AMR. This gap suggests a need for well-designed and robust studies that assess and evaluate the impact of interventions and target animal health professionals and farmers in Africa.